Factors that affect in the development of reading comprehension process of 4th year english major students when reading authentic texts - Landaverde, Carlos Alfredo
Reading comprehension is an important skill that promotes the development of different academic activities of students. It helps them decoding a text, analyzing, interpreting and expressing their own opinions about any written material. The ability to read and understand written material is very important in the civilized world. Today college students need to have developed a strong ability to comprehend, every kind of written information to struggle with the academic activities that professors at the university work with. The students, as they progress in their education, face expository or explanatory and argumentative texts, and this need grows, so they need to understand and produce in relation to what they read. But, the real fact was that most of a great number of Salvadorian college students had not well developed this skill . It was not a secret, that, there were many students in the Foreign Language Department at the University of El Salvador that had poor reading comprehension skills and had difficulties doing their analysis in reading tasks. Based on the last idea and the experience as students from “Licenciatura en Idioma Inglés Opción: Enseñanza” and the different difficulties faced when being in the fourth academic year of the major, it was really difficult to understand written material which was not graded by the teachers; in other words, authentic texts. At this level, students had to deal with subjects where it was mandatory to read and analyze information from real context as for example to read some chapters of books written by academic writers.